Dynamics of The Sulinggih Candidate Aguron-Guron System in Denpasar City - Arka, I Made; Sudiana, I Gusti Ngurah; Putrawan, I Nyoman Alit (PT. Hafasy Dwi Nawasena, 2025)
The position of Sulinggih has requirements, job descriptions containing duties and authorities. In Hindu terms, it is called Sasana Kawikon. However, it is not easy for a Sulinggih to maintain Sasana Kawikon. This dissertation comprehensively discusses the existence of the Aguron-guron system for prospective Sulinggih, the development of the Aguron-guron system for prospective Sulinggih, and the implications of the Aguron-guron system for prospective Sulinggih on the diversity of Hindus in Denpasar. The method used is a qualitative method. The data for this study include information from Paruman Pandita Parisada Hindu Dharma Indonesia, Denpasar. The results of the study show that (1) the existence of the Aguron-guron system for prospective Sulinggih in Denpasar has improved with the supervision of the Parisada Hindu Dharma Indonesia of Denpasar through Diksa Pariksa, the rights and obligations of prospective Sulinggih and Sulinggih from Pesemetonan are the same, the requirements to become Sulinggih are determined by Parisada Hindu Dharma Indonesia of Denpasar, the references used are Siwa Sanana, Rsi Sasana Catur Yuga, Sila Kramaning Aguron-guron, Purwa Bhasita Krama, Dharma Kapanditan, Purba Somi, and Raja Pati Gondala. (2) the development of the Aguron-guron system for prospective Sulinggih includes improving human resources, regulations or rules are as guidebooks, Griya/Pasraman is as a place to learn Sulinggih, Guru or Nabe is as a benchmark for fostering prospective Sulinggih, the process of becoming Sulinggih is left to the Pesemetonan. (3) The implications of the Aguron-guron system for prospective Sulinggih include Theology, Anthropology, Social, Economics and Pedagogy.